(untitled) (International Journal of Environmental Sciences, 2025)
The purpose of this study is to analyze the utiligation of artificial intelligence to support climent smart agriculture in India. This paper involve in descriptive analysis which focused on the role of AI, how it transform the life of farmer, how it leads to change in the agriculture operation, awareness of the farmer and scope of the AI, in climent smart agriculture. The digital world that we stand today is due to the different advancement in automation and science, modernization and latest innovation. The automation in agriculture is the main concern and the emerging subject across the world. The population in increasing tremendously and with this increase the demands of food and employment is also increasing. AI in smart agriculture has bought and agricultural revolution. The main concern of this paper is to audit the various applications of AI in agricultures such as for irrigation, sparing, weeding with help of sensor and others embedded in robots and drone. This technology save to excess use of water, pesticide, herbicides maintain the fertility of the soil, also help in the efficient use of man power and elevate the productivity and improve the quality. This paper present insights on the various application of technology advancement in agriculture such as digital agriculture, smart farming or internet of agriculture technology (IoAT), crop management, crop protection with the importance of ICT in climent smart agriculture farming and focus on improving the life of the rural poor by introducing various new technology to them for developing more relevant and rapidly functioning technologies.